Analisis Kausalitas Kesejahteraan Masyarakat dengan Pertumbuhan Ekonomi di Provinsi Kalimantan Tengah - Try Santi Evelina Situmorang; Alexandra Hukom (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of this study is to investigate the causal relationship between economic growth and community welfare. The time series data used covers the years 2014-2023. Vector Error Correction Model (VECM) is the technique used for data analysis. The study found that although there is no substantial correlation between economic growth and community welfare, there is a causal relationship between the two, which suggests that the causal relationship is not unidirectional. In addition, only community welfare has a short-term impact on economic growth; there is no long-term relationship between the two.